IgG4-Related Hashimoto's Thyroiditis - A New Variant of a Well Known Disease - Vara Luiz, H (2014)
Hashimoto's thyroiditis (HT) has been characterized for many years as a well-defined clinicopathologic entity, but is now considered a heterogeneous disease. IgG4-related HT is a new subtype characterized by thyroid inflammation rich in IgG4-positive plasma cells and marked fibrosis. It may be part of the systemic IgG4-related disease. We report a case of a 56-year-old Portuguese man who presented with a one-month history of progressive neck swelling and dysphagia. Laboratory testing revealed increased inflammatory parameters, subclinical hypothyroidism and very high levels of thyroid autoantibodies. Cervical ultrasound (US) demonstrated an enlarged and heterogeneous thyroid gland and two hypoechoic nodules. US-guided fine needle aspiration cytology was consistent with lymphocytic thyroiditis. The patient was submitted to total thyroidectomy and microscopic examination identified typical findings of HT, marked fibrosis limited within the thyroid capsule and lymphoplasmacytic infiltration, with >50 IgG4-positive plasma cells per high-power field and an IgG4/IgG ratio of >40%. After surgery, serum IgG4 concentration was high-normal. Symptoms relief and reduction in laboratory inflammatory parameters were noticed. Thyroid function is controlled with levothyroxine. To our knowledge we report the first case of IgG4-related HT in a non-Asian patient. We also perform a review of the literature regarding IgG4-related disease and IgG4-related HT. Our case highlights this new variant of the well known HT, and helps physicians in recognizing its main clinical features, allowing for proper diagnosis and treatment.